Analysis of exhaust manifold to improve the engine performance - Krishnara J, C; Rajesh Ruban, S; Subramani, N (International Journal of Engineering and Technology, 2018)
The aim of the work is to analyze the performance of the engine exhaust manifold. Because the engine exhaust manifold is a significant factor in the engine performance. In this work the manifold design is prepared with the help of CAD software and it is analyzed by the ANSYS. This CFD and thermal analysis also done to check the performance of the redesigned exhaust manifold. The aim of CFD simulations performed to investigate the volumetric efficiency behaviour of an exhaust.